PENGARUH EKSTRAK KOMPOS LIMBAH BUAH KAKAO DAN PEMUPUKAN P TERHADAP AL MONOMERIK DALAM TANAH DAN SERAPAN P OLEH JAGUNG PADA OXIC DYSTRUDEPT - Rezi Amelia (Universitas Tadulako, 2013)
The study was conducted to determine the effect of extract of cacao fruit waste compost at various levels of P fertilizer application on monomeric Al in the soil and acidity characteristics of Palolo Oxic Dystrudepts. In addition, this study was aimed to determine the effect of extract of cacao fruit waste compost at various levels of P fertilizer application on P uptake, P fertilization efficiency and maize growth in the Oxic Dystrudepts. The experiment was carried out in two phases. Phase I wasa soil experiment without plant, while in phase II, the experiment was conducted in a greenhouse using maize as an indicator plant. The experimental design used wasatwo-factorial randomized complete design, where the first factor was rate of cacao fruit waste compost extract produced from 8-day fermentation process(D) consisting of D0 = 0ℓ.ha-1 (control), D1 = 500ℓ.ha-1, D2 = 1000ℓ.ha-1, and D3 = 2000ℓ.ha-1. The second factor was rate of SP-27 (P) fertilizer consisting of P0 = 0 kg.ha-1, P1 = 50 kg.ha-1, P2 = 100 kg.ha-1, and P3 = 200 kg.ha-1. Each treatment was replicated three times, hence, there were 4 x 4 x 3 = 48 experimental plots. The results showed that increasing rates of cacao fruit waste compost extract application at all rates of P fertilizer significantly decreased monomeric Alconcentration in the soil solution, and thismonomeric Al concentration also decreased with increasing rates of P fertilizer at all rates of cacao fruit waste compost extract application. The application of compost extract at2000ℓha-1 combined with P fertilizer at200 kgha-1represented the best combination since it decreased the concentration of monomeric Al in the soil solution from 650.8μM to 339.7μM. The results alsoshowed that application of cacao fruit waste compost extract with increasing rates significantly decreased soil exchangeable Al and increased soil pH, P uptake efficiency of maize, soil available P, soil organic C level, soil CEC, plant dry weight, and P concentration and uptake of maize. In the experiment with maize as an indicator plant, P concentration and P uptake in maize tissue also increased with increasing in P fertilizerrate. Application of P fertilizer at the rate of 200 kg Pha-1 produced the highest P concentration (0.50%) and P uptake (238.61 mg P plant-1) in the plant at 38 days after planting (DAP). P uptake efficiency increased with increasing rates of cacao fruit waste compost extract, while the efficiency of P uptake decreased with increasing rates of P fertilizer application. Key Words : Cacao fruit waste, compost extract, monomericAl, Oxic Dystrudepts, and P fertilizer.